Segementni prelomi tibije lečeni fiksatorom po Ilizarov-u - Tomić, Slavko; Slavković, Nemanja; Tulić, Goran; Baljozović, Andreja; Jovanović, Želimir; Mirković, Milan; Rajković, Stanislav; Bogosavljević, Nikola; Šaponjski, Dušan; Mihajlović, Sladjana; Jeremić, Danilo (Vojnosanitetski pregled, 2021)
Background/Aim. Segmental fractures represent complex tibial injuries, featuring a unique fracture type that is most commonly caused by high-energy trauma. These fractures are considered to be a treatment challenge for orthopaedic surgeons due to their sporadic presentation, wide zone of soft tissue injury, and increased rate of complications. They are characterized by a highly unstable intermediary segment and a high rate of open fractures.  The method of Ilizarov with its characteristics could offer many advantages over the existing operative techniques. This method, using a percutaneous approach, minimizes the intraoperative trauma and avoids the additional compromising of the biological environment at the fracture site. The aim of this study was to evaluate the results of the Ilizarov fixator in the treatment of segmental tibial fractures. Methods. We analyzed 30 patients treated with the Ilizarov fixator between 2012 and 2017. The average age of patients was 36 years (from 24 to 65). The most common mechanism of injury was a road traffic accident. Open fractures were noted in 22 cases. All fractures were reduced using indirect percutaneous techniques with a great focus on achieving the correct length, rotation, and axial alignment of fragments. All patients were advised to bear weight as tolerated from the second postoperative day. Bone healing and functional results were evaluated according to the criteria established by the Association for the Study and Application of the Method of Ilizarov. Results. Bone healing was achieved in all patients. The average time to union was 25 weeks (19 to 36 weeks).  Bone results were excellent in 23 patients, good in five, and fair in two patients. Functional results were excellent in 22 cases, good in 5, and fair in three cases. Eight patients had minor pin-tract infections, successfully treated with oral antibiotics. Patients were without any major complications. Conclusion. The Ilizarov method is a safe and efficient treatment modality for segmental tibial fractures.
Keywords: tibial fractures; external fixators; ilizarov technique; recovery of function